PENERAPAN ASAS PRADUGA TAK BERSALAH DALAM PERKARA OPERASI TANGKAP TANGAN OLEH KOMISI PEMBERANTASAN KORUPSI DALAM PERSPEKTIF KUHAP - Moh. Bachrul Ulum (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTThis scientific paper is the result of research as a final project in completing studies at the Faculty of Law of the University of August 17, 1945, Samarinda. normative juridical research, meaning that the research is conducted from materials, sources and legal doctrine with the formulation of the problem: 1) How the application of the principle of presumption of innocence in arresting operations by the Criminal Eradication Commission in the perspective of Law No. 8 of 1981 concerning the Law Code of Law Criminal Procedure (KUHAP)?, 2) What is the legal effect on the application of the presumption of innocence in an arrest operation by the Corruption Eradication Commission when it is not in accordance with Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP) ?.The last few years Operation Arrest (OTT) by the Corruption Eradication Commission (KPK) has become the public spotlight of the Indonesian people and even the world, because the OTT conducted by the KPK does not look indiscriminately, from high-ranking officials to Regents and Mayors including Legislative Members and Law Enforcement Members Law, both Judges, Prosecutors, Court Clerks, and Advocates even high-ranking Police officers. On the other hand, the public gave an appreciation of the performance of the KPK on the other hand many questioned the performance of the KPK including OTT. These pros and cons inspire the author to conduct research on OTT by the KPK on the application of the presumption of innocence in the perspective of the Criminal Procedure Code.OTT by the KPK is not without legal basis, the KPK conducts OTT based on its duties and functions as regulated in Act Number 19 of 2019 concerning the Corruption Eradication Commission, and based on Article 1 number 19 and 18 paragraph (2) of the Criminal Procedure Code. Application of the principle of presumption of innocence can be applied within the framework of the actions of investigators, investigators, public prosecutors, ranging from appearances, detention, prosecution to court decisions that have legal force (Kracht van gewijisde), the principle of presumption of innocence is a manifestation of guarantees and legal protection individually by the State. Therefore, if there are law enforcers including the Corruption Eradication Commission (KPK) carrying out their duties and functions in violation of the presumption of innocence, that is, arbitrary arrests can be considered unlawful so that they can be pre-judged and considered as committing human rights violations.Keywords: Principles of Presumption of Innocence, Operation Arrest, Corruption Eradication Commission, Criminal Procedure Code